Markedly elevated neonatal immunoreactive trypsinogen levels in the absence of cystic fibrosis gene mutations is not an indication for further testing. Issue 3 (21st October 2005) - Massie, J; Curnow, L; Tzanakos, N; Francis, I; Robertson, C F
Abstract : Aims: To investigate the immunoreactive trypsinogen (IRT) values above the usual 99th centile laboratory cut-off and determine the value of offering further testing to those infants with a markedly elevated IRT but no cystic fibrosis transmembrane regulator (CFTR) gene mutation identified by the screening programme. Methods: All babies born in Victoria, Australia, between 1991 and 2003, were screened by IRT followed by CF gene mutation analysis. Results: Of the 806 520 babies born, 9268 with the highest IRT levels had CFTR mutation analysis. There were 123 ΔF508 homozygotes and 703 heterozygotes (86 with CF, 617 carriers). A total of 8442 babies had no CFTR gene mutation, of whom 18 (0.21%) had CF. The total number of CF babies with IRT greater than the laboratory cut-off was 227 (2.4%). The IRT results of the CF patients were distributed normally, with the majority above the laboratory cut-off of newborn IRT results. There was no evidence of an excess of babies with CF in the very highest levels of IRT above the 99th centile. Conclusions: Only a small proportion of babies with a neonatal IRT >99th centile have CF. Additional CF testing for infants with an elevated IRT but no CFTR gene mutation has an extremely low yield, no matter how high the IRT result.